Electrolyte, sodium secondary battery, and electric device
Patent Information
- Application Number
- CN202611323625.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-09
- Filing Date
- 2024-09-19
- Publication Date
- 2026-10-30
AI Technical Summary
但是,由于钠二次电池存在产气问题严重影响了其电池的电学性能,无法满足新一代电化学体系的应用需要
Smart Images

Figure CN123018141A_ABST
Abstract
Description
[0001] This application is a divisional application based on the invention with application number 202480083656.6, application date September 19, 2024, applicant CATL, and invention title "Electrolyte, Sodium Secondary Battery and Electrical Device". Technical Field
[0002] This application relates to the field of sodium battery technology, and more particularly to an electrolyte, a sodium secondary battery, and an electrical device. Background Technology
[0003] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.
[0004] Compared to lithium-ion batteries, sodium-based batteries have a greater competitive advantage due to the abundance and wide distribution of sodium resources. However, the gas generation problem in sodium-based batteries severely affects their electrical performance, making them unable to meet the application needs of next-generation electrochemical systems. Summary of the Invention
[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide an electrolyte that improves the stability of the SEI film, thereby reducing the degree of gas generation during the cycling and storage process of sodium secondary batteries, improving the storage performance, fast charging performance and cycling performance of sodium secondary batteries, and comprehensively improving the performance of sodium secondary batteries.
[0006] A first aspect of this application provides an electrolyte for a sodium secondary battery, comprising a first additive and a second additive. The first additive comprises a cyclic ester compound containing sulfur, and the second additive comprises one or more of fluorosulfonate and difluorophosphate. The cyclic ester compound comprises a compound with the structure shown in Formula I. Formula I, In formula I, R1 includes or R2 and R3 each independently include at least one of the following: a hydrogen atom, a C1-C6 alkyl group, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy group, a C1-C3 olefin group, an ester group, a cyano group, and a sulfonic acid group. R4 includes at least one of the following: an oxygen atom, a C1-C6 alkyl group, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, and a C1-C3 haloalkoxy group.
[0007] The first additive, comprising a cyclic ester compound containing sulfur, and / or the second additive, a difluorophosphate, can preferentially reduce the SEI film at the negative electrode compared to the solvent in the electrolyte. This generates sulfuric acid-based components and other components containing fluorine, sulfur, or phosphorus within the SEI film, reducing its solubility in the electrolyte and thus significantly decreasing gas production. Simultaneously, through the synergistic effect of both additives, the stability and flexibility of the SEI film are improved, reducing the DC resistance of the sodium secondary battery, enhancing its storage and fast-charging performance, and comprehensively improving its cycle performance.
[0008] The aforementioned cyclic ester compounds can generate sulfate-based components in the SEI film, which can cover the surface of the negative electrode to reduce the degree of exposure of the negative electrode to the electrolyte, reduce side reactions and gas generation, and improve the performance of sodium secondary batteries.
[0009] In any implementation, in formula I, R1 includes or R2 and R3 each independently include at least one of a hydrogen atom, a C1-C6 alkyl group, a C1-C3 haloalkyl group, and a C1-C3 olefinic group. R4 includes at least one of an oxygen atom, a C1-C6 alkyl group, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, and a C1-C3 haloalkoxy group.
[0010] In any implementation, the structure shown in Formula I includes , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , At least one of them.
[0011] All of the above-mentioned cyclic ester compounds can generate sulfate-based components in the SEI film. In particular, R2, R3, and R4 each independently include C1-C6 alkyl groups or C1-C3 haloalkyl groups, which are easier to form films quickly and can cover the surface of the negative electrode to reduce the degree of exposure of the negative electrode to the electrolyte, reduce side reactions and gas generation, and improve the performance of sodium secondary batteries.
[0012] In any embodiment, the fluorosulfonate comprises a compound represented by Formula II. (FSO3) y1 M1 y1+ Formula II In Formula II, M1 y1+ Including Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the following, where y1 = 1, 2, or 3.
[0013] In any embodiment, the difluorophosphate comprises a compound of formula III. (PO2F2) y2 M2 y2+ Formula III In Equation III, M2 y2+ Including Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the following, y2 = 1, 2 or 3.
[0014] The aforementioned fluorosulfonates or difluorophosphates can form other components containing fluorine, sulfur, or phosphorus in the SEI film. This SEI film can improve the overall stability of the SEI film on the surface of the negative electrode, reduce the degree of oxidation and decomposition of the SEI film as well as its solubility in the electrolyte solvent, thereby improving the storage performance of sodium secondary batteries.
[0015] In any embodiment, the mass ratio of the first additive to the second additive is 0.02 to 500.
[0016] By controlling the mass ratio of the first and second additives within a suitable range, the solubility of the SEI film in the electrolyte can be reduced, thereby significantly decreasing the degree of gas production. Simultaneously, through their synergistic effect, the storage performance and DC resistance of the sodium secondary battery can be balanced, comprehensively improving the performance of the sodium secondary battery.
[0017] In any embodiment, the mass ratio of the first additive to the second additive is 0.2 to 100.
[0018] Further controlling the mass ratio of the first additive to the second additive to 0.2~100 is beneficial to further improve the cycle performance of sodium secondary batteries.
[0019] In any embodiment, the mass content of the cyclic ester compound is 0.01% to 5% based on the total mass of the electrolyte.
[0020] Controlling the mass content of cyclic ester compounds containing sulfur within a suitable range is beneficial for generating sulfuric acid components in the SEI membrane. This reduces the degree of rupture of the SEI membrane caused by the expansion of the sodium secondary battery during cycling, thereby improving the overall protective capability of the SEI membrane and enhancing the storage performance of the sodium secondary battery.
[0021] In any embodiment, the mass content of the cyclic ester compound is 0.1% to 2% based on the total mass of the electrolyte.
[0022] Further controlling the mass content of cyclic ester compounds containing sulfur to 0.1%~2% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0023] In any embodiment, the mass content of the fluorosulfonate is 0.001% to 5% based on the total mass of the electrolyte.
[0024] Controlling the mass content of fluorosulfonate within a suitable range is beneficial for forming components containing fluorine and sulfur elements in the SEI membrane, thereby effectively improving the overall stability of the interfacial SEI membrane and reducing the solubility of the interfacial SEI membrane in the electrolyte. This significantly reduces gas production and improves the cycle performance and storage performance of sodium secondary batteries.
[0025] In any embodiment, the mass content of the fluorosulfonate is 0.1% to 2% based on the total mass of the electrolyte.
[0026] Further controlling the mass content of fluorosulfonate to 0.1%~2% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0027] In any embodiment, the mass content of the difluorophosphate is 0.001% to 5% based on the total mass of the electrolyte.
[0028] Controlling the mass content of difluorophosphate within a suitable range is beneficial for forming components containing fluorine and phosphorus elements in the SEI membrane, thereby effectively improving the overall stability of the interface SEI membrane. At the same time, it reduces the solubility of the interface SEI membrane in the electrolyte, thus greatly reducing the degree of gas production and improving the cycle performance and storage performance of sodium secondary batteries.
[0029] In any embodiment, the mass content of the difluorophosphate is 0.1% to 2% based on the total mass of the electrolyte.
[0030] Further controlling the mass content of difluorophosphate to 0.1%~2% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0031] In any embodiment, the electrolyte further includes a third additive, which includes one or more of fluoroethylene carbonate, difluoroethylene carbonate, vinylene carbonate, ethylene ethylene carbonate, maleic anhydride, succinic anhydride, and triallyl phosphate.
[0032] The introduction of a third additive containing unsaturated functional groups is beneficial for the formation of a more soluble SEI film on the surface of the negative electrode sheet, which is more advantageous than the formation of a solvent in the electrolyte. This reduces the overall solubility of the SEI film in the electrolyte, thereby reducing the degree to which the negative electrode sheet is exposed to the electrolyte, and thus reducing the degree of gas production. This comprehensively improves the performance and lifespan of sodium secondary batteries.
[0033] In any embodiment, the mass content of the third additive is 0.01% to 10% based on the total mass of the electrolyte.
[0034] By controlling the mass content of the third additive within a suitable range, sufficient amounts of the third additive can be provided to form a SEI film with higher solubility, thereby reducing the overall solubility of the SEI film in the electrolyte, reducing the degree of exposure of the negative electrode sheet in the electrolyte, and thus reducing the degree of gas production, thereby comprehensively improving the performance of the battery.
[0035] In any embodiment, the mass content of the third additive is 0.1% to 5% based on the total mass of the electrolyte.
[0036] Controlling the mass content of the third additive to 0.1%~5% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0037] In any embodiment, the electrolyte comprises a sodium salt, which includes one or more of NaPF6, NaBF4, NaN(SO2F)2, NaClO4, NaAsF6, NaB(C2O4)2, and NaBF2(C2O4).
[0038] In any embodiment, the electrolyte includes a solvent, which includes one or more of the following: chain carbonate solvents, chain carboxylic acid ester solvents, cyclic carbonate solvents, and ether solvents.
[0039] In any embodiment, the chain carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate. The chain-like carboxylic acid ester solvent includes one or more of methyl formate, ethyl formate, methyl propionate, ethyl propionate, propyl propionate, ethyl butyrate, methyl acetate, ethyl acetate, and propyl acetate. The cyclic carbonate solvent includes one or more of the following: ethylene carbonate, propylene carbonate, butene carbonate, vinylene carbonate, fluoroethylene carbonate, ethylene sulfite, propylene sulfite, vinylethylene carbonate, 4-ethynyl-1,3-dioxacyclopentan-2-one, cis-4,5-difluoro-1,3-dioxacyclopentan-2-one, and trans-4,5-difluoro-1,3-dioxacyclopentan-2-one. The ether solvents include one or more of dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, 1,2-diethoxyethane, and 1,2-dibutoxyethane.
[0040] The second aspect of this application provides a sodium secondary battery, including a positive electrode, a negative electrode, and an electrolyte provided in the first aspect of this application.
[0041] In any embodiment, the positive electrode sheet includes a positive current collector and a positive electrode material layer located on at least one side of the positive current collector. The positive electrode material layer includes a positive electrode active material, which includes at least one of layered transition metal oxides, Prussian blue compounds, and polyanionic compounds.
[0042] In any embodiment, the layered transition metal oxide includes Na. x Mn a Fe b Ni c M d N e O 2-δ Q f Wherein, M includes at least one of Ti, Li, V, Cr, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, Mg, and Al; N includes at least one of Si, P, B, S, and Se; Q includes at least one of F, Cl, and N; 0.66 ≤ x ≤ 1; 0 <a≤0.7,0<b≤0.7,0<c≤0.23,0≤d<0.3,0≤e≤0.3,0≤f≤0.3,0≤δ≤0.3,a+b+c+d+e=1,0<e+f≤0.3,0<(e+f) / a≤0.3,0.2≤d+e+f≤0.3,(b+c) / a≤1.5。
[0043] In any embodiment, the positive electrode active material comprises a layered transition metal oxide containing Cu. The ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Cu in the positive electrode active material is greater than or equal to 0.002.
[0044] Introducing Cu into the positive electrode active material is beneficial to the stability of the material's structure. Simultaneously, Cu in the positive electrode active material can also oxidize with sulfur-containing cyclic ester compounds at the positive electrode interface to form insoluble Cu salts, which helps reduce the degree of gas generation caused by the oxidative decomposition of the electrolyte on the positive electrode side. Controlling the ratio of the mass content of cyclic ester compounds in the electrolyte to the mass content of Cu in the positive electrode active material within an appropriate range can effectively reduce the degree of gas generation caused by the oxidative decomposition of the electrolyte on the positive electrode side.
[0045] In any embodiment, the mass content of Cu element in the positive electrode active material is less than or equal to 23%.
[0046] Controlling the Cu content in the positive electrode active material within a suitable range is beneficial for providing enough Cu to increase the stability of the positive electrode active material structure, while also reducing the degree of performance degradation of sodium secondary batteries caused by excessive Cu content leading to oxidative decomposition in the electrolyte.
[0047] In any embodiment, the Cu element in the positive electrode active material has a mass content of 6.5% to 18%.
[0048] Further controlling the Cu content in the positive electrode active material to 6.5%~18% is beneficial to further balance the storage performance and fast charging performance of sodium secondary batteries.
[0049] In any embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer located on at least one side of the negative electrode current collector, wherein the negative electrode material layer includes Ca element; The ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Ca in the negative electrode material layer is greater than or equal to 1.
[0050] Introducing calcium (Ca) into the negative electrode active material helps reduce the formation of sodium dendrites. Simultaneously, the introduction of Ca facilitates the formation of a calcium salt-containing SEI film with sulfur-containing cyclic ester compounds, thereby improving the overall toughness of the SEI film and reducing the DC impedance of the sodium secondary battery. Maintaining the ratio of the mass content of cyclic ester compounds in the electrolyte to the mass content of Ca in the negative electrode material layer within a suitable range allows for a balance between the storage performance and fast-charging performance of the sodium secondary battery.
[0051] In any embodiment, the mass content of Ca element in the negative electrode material layer is 0.1ppm to 3000ppm.
[0052] By controlling the mass content of Ca in the negative electrode material layer within a suitable range, it is possible to form an SEI film containing calcium salt components, improve the overall toughness of the SEI film, and reduce the DC resistance of the sodium secondary battery. At the same time, it is possible to reduce the degree of performance degradation of the sodium secondary battery caused by the increase of DC resistance, thus balancing the storage performance and fast charging performance of the sodium secondary battery.
[0053] In any embodiment, the mass content of Ca element in the negative electrode material layer is 50ppm to 1000ppm.
[0054] In any embodiment, the mass content of Ca element in the negative electrode material layer is 100ppm to 1000ppm.
[0055] Further controlling the mass content of Ca in the negative electrode material layer to 50ppm~1000ppm or 100ppm~1000ppm is beneficial to further improve the storage performance and fast charging performance of sodium secondary batteries.
[0056] In any embodiment, the negative electrode material layer further includes a negative electrode active material, which includes one or more of hard carbon, metallic sodium, tin alloy, and metal oxide.
[0057] In any embodiment, at a charging rate of 0.05C, the capacity of the negative electrode sheet within the charging range of 0.5V to 1V is 9mAh / g to 140mAh / g.
[0058] Within the charging range of 0.5V to 1V, controlling the capacity of the negative electrode within a suitable range can provide sufficient capacity to meet the energy density requirements of sodium secondary batteries, while also reducing the degree of performance degradation caused by excessive gas production due to excessive negative electrode capacity.
[0059] In any embodiment, at a charging rate of 0.05C, the capacity of the negative electrode sheet within the charging range of 0.5V to 1V is 18mAh / g to 70mAh / g.
[0060] Within the charging range of 0.5V to 1V, further controlling the capacity of the negative electrode sheet to 18mAh / g to 70mAh / g is beneficial for further balancing the energy density and storage performance of sodium secondary batteries.
[0061] A third aspect of this application provides an electrical device, including a sodium secondary battery as described in the second aspect of this application. Attached Figure Description
[0062] Figure 1 This is a schematic diagram of a sodium secondary battery according to one embodiment of this application.
[0063] Figure 2 yes Figure 1 An exploded view of a sodium secondary battery according to an embodiment of this application is shown.
[0064] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0065] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0066] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0067] Figure 6This is a schematic diagram of an electrical device using a sodium secondary battery as a power source according to an embodiment of this application.
[0068] Explanation of reference numerals in the attached figures: 1 Battery pack; 2 Upper casing; 3 Lower casing; 4 Battery module; 5 Sodium secondary battery; 51 Housing; 52 Electrode assembly; 53 Top cover assembly Detailed Implementation The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the electrolyte, sodium secondary battery, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0069] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0070] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0071] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0072] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0073] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0074] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0075] Gas generation in sodium-ion batteries severely impacts their electrical performance, especially at low voltages on the negative electrode side. Typically, film-forming additives are introduced into the electrolyte to form a solid electrolyte interphase (SEI) film on the negative electrode surface. The formation of the SEI film can, to some extent, prevent further electrolyte decomposition and gas generation, thus improving the performance of the sodium-ion battery. However, gas generation problems persist during cycling and storage. Therefore, it is necessary to design an electrolyte that meets the application requirements of next-generation electrochemical systems.
[0076] Electrolyte Based on this, this application proposes an electrolyte for sodium secondary batteries, comprising a first additive and a second additive. The first additive comprises a cyclic ester compound containing sulfur, and the second additive comprises one or more of fluorosulfonate and difluorophosphate. The cyclic ester compound comprises a compound with the structure shown in Formula I. Formula I, In formula I, R1 includes or R2 and R3 each independently include at least one of the following: hydrogen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, C1-C3 alkoxy group, C1-C3 haloalkoxy group, C1-C3 olefin group, ester group, cyano group, and sulfonic acid group; R4 includes at least one of the following: oxygen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, C1-C3 alkoxy group, and C1-C3 haloalkoxy group.
[0077] In this article, "cyclic ester compounds containing sulfur" refers to compounds containing sulfonic acid groups or sulfinic acid groups and forming a ring, which can be a five-membered ring or a six-membered ring.
[0078] In this article, "fluorosulfonate" refers to a salt with an anion concentration of 100 ppm. Cations include, but are not limited to, Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the compounds.
[0079] In this article, "difluorophosphate" refers to phosphate with anion concentration of 1000 ppm. Cations include, but are not limited to, Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the compounds.
[0080] In some embodiments, the second additive includes fluorosulfonate.
[0081] In some embodiments, the second additive includes difluorophosphate.
[0082] In some embodiments, the second additive includes fluorosulfonate and difluorophosphate.
[0083] Studies have found two main reasons why sodium-ion batteries still produce significant gas during cycling and storage at low voltages: First, the negative electrode potential of sodium-ion batteries is 0.3V higher than that of lithium-ion batteries. A higher potential drives the formation of an SEI film, primarily composed of organic components, using film-forming additives. However, these organic components are unstable and begin to oxidize and decompose at 0.5V, generating a large amount of gas. Second, the SEI film in sodium-ion batteries mainly consists of alkyl sodium carbonate formed by solvent reduction. Alkyl sodium carbonate has high solubility in the electrolyte solvent. Dissolution of the SEI film exposes the negative electrode to the electrolyte, causing side reactions between the negative electrode and the electrolyte that produce a large amount of gas.
[0084] The first additive, comprising a cyclic ester compound containing sulfur, and the second additive, comprising fluorosulfonate and / or difluorophosphate, can preferentially reduce the SEI film at the negative electrode compared to the solvent. This generates sulfate-based components and other components containing fluorine, sulfur, or phosphorus within the SEI film, reducing its solubility in the electrolyte and thus significantly decreasing gas production. Simultaneously, through the synergistic effect of both additives, the stability and flexibility of the SEI film are improved, reducing the DC resistance of the sodium secondary battery, enhancing its storage and fast-charging performance, and comprehensively improving its cycle performance.
[0085] In some implementations, R1 in Formula I includes or R2 and R3 each independently include at least one of hydrogen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, and C1-C3 olefin group, and R4 includes at least one of oxygen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, C1-C3 alkoxy group, and C1-C3 haloalkoxy group.
[0086] In some implementations, R1 in Formula I includes or R2 and R3 each independently include at least one of C1-C6 alkyl, C1-C3 haloalkyl, and C1-C3 olefin, and R4 includes at least one of oxygen atom and methylene.
[0087] In some implementations, R1 in Formula I includes or R2 and R3 each independently include C1-C6 alkyl groups and / or C1-C3 haloalkyl groups, and R4 includes at least one of an oxygen atom and a methylene group.
[0088] The aforementioned cyclic ester compounds can generate sulfate-based components in the SEI film, which can cover the surface of the negative electrode to reduce the degree of exposure of the negative electrode to the electrolyte, reduce side reactions and gas generation, and improve the performance of sodium secondary batteries.
[0089] In some embodiments, the structure shown in Formula I includes Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9, Formula I-10, Formula I-11, Formula I-12, Formula I-13, Formula I-14, Formula I-15, Formula I-16, Formula I-17, Formula I-18, Formula I-19, Formula I-20, Formula I-21, Formula I-22, Formula I-23, Formula I-24, Formula I-25, Formula I-26, Formula I-27, Formula I-28, Formula I-29, Formula I-30, Formula I-31, Formula I-32, Formula I-33, Formula I-34, Formula I-35, Formula I-36, At least one of Formula I-37.
[0090] The aforementioned cyclic ester compounds containing sulfur can all form sulfate-based components in the SEI film. In particular, R2, R3, and R4, each independently comprising a C1-C6 alkyl group or a C1-C3 haloalkyl group, facilitate faster film formation. This SEI film can cover the surface of the negative electrode, reducing its exposure to the electrolyte, minimizing side reactions and gas generation, and improving the performance of sodium secondary batteries. Furthermore, the independent selection of R2 and R3 from C1-C3 haloalkyl groups allows for better control of the band structure of the cyclic ester compounds, lowering the LUMO energy level and facilitating reduction and decomposition to form the SEI film. Additionally, the presence of sulfur (F) in the SEI film contributes to improved overall SEI film stability.
[0091] In some embodiments, fluorosulfonates include compounds represented by Formula II. (FSO3) y1 M1 y1+ Formula II In Formula II, M1 y1+ Including Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the following, where y1 = 1, 2, or 3.
[0092] In some implementations, M1 y1+ Including Li + Na + One or more of them, y1=1.
[0093] In some embodiments, the fluorosulfonate includes one or more of sodium fluorosulfonate, lithium fluorosulfonate, potassium fluorosulfonate, magnesium fluorosulfonate, and iron fluorosulfonate. In some embodiments, the fluorosulfonate includes sodium fluorosulfonate. In some embodiments, the fluorosulfonate includes lithium fluorosulfonate.
[0094] In some embodiments, the difluorophosphate includes the compound shown in Formula III. (PO2F2) y2 M2 y2+ Formula III In Equation III, M2 y2+ Including Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the following, y2 = 1, 2 or 3.
[0095] In some implementations, M2 y2+ Including Li + Na+ One or more of them, y2=1.
[0096] In some embodiments, the difluorophosphate includes one or more of sodium difluorophosphate, lithium difluorophosphate, potassium difluorophosphate, magnesium difluorophosphate, and iron difluorophosphate. In some embodiments, the difluorophosphate includes sodium difluorophosphate. In some embodiments, the difluorophosphate includes lithium difluorophosphate.
[0097] The aforementioned fluorosulfonates or difluorophosphates can form components containing fluorine, sulfur, or phosphorus in the SEI film. This SEI film can improve the overall stability of the SEI film on the surface of the negative electrode, reduce the degree of overall oxidation and decomposition of the SEI film, and its solubility in the electrolyte solvent, thereby improving the storage performance of sodium secondary batteries.
[0098] In some embodiments, the mass ratio of the first additive to the second additive is 0.02 to 500. In some embodiments, the mass ratio of the first additive to the second additive can be selected as 0.02, 0.05, 0.1, 0.2, 0.5, 1, 3, 5, 7, 10, 30, 50, 80, 100, 150, 200, 250, 300, 350, 400, 450, 500, or a value within the range formed by any two of the above points.
[0099] By controlling the mass ratio of the first and second additives within a suitable range, the solubility of the SEI film in the electrolyte can be reduced, thereby significantly decreasing the degree of gas production. Simultaneously, through their synergistic effect, the storage performance and DC resistance of the sodium secondary battery can be balanced, comprehensively improving the performance of the sodium secondary battery.
[0100] In some embodiments, the mass ratio of the first additive to the second additive is 0.2 to 100.
[0101] Further controlling the mass ratio of the first additive to the second additive to 0.2~100 is beneficial to further improve the cycle performance of sodium secondary batteries.
[0102] In some embodiments, the mass content of the cyclic ester compound is 0.01% to 5% based on the total mass of the electrolyte. In some embodiments, the mass content of the cyclic ester compound may be selected from 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or a value within a range consisting of any two of the above, based on the total mass of the electrolyte.
[0103] Controlling the mass content of cyclic ester compounds containing sulfur within a suitable range is beneficial for generating sulfuric acid components in the SEI membrane. This reduces the degree of rupture of the SEI membrane caused by the expansion of the sodium secondary battery during cycling, thereby improving the overall protective capability of the SEI membrane and enhancing the storage performance of the sodium secondary battery.
[0104] In some embodiments, the mass content of the cyclic ester compound is 0.1% to 2% based on the total mass of the electrolyte.
[0105] Further controlling the mass content of cyclic ester compounds containing sulfur to 0.1%~2% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0106] In some embodiments, the mass content of fluorosulfonate is 0.001% to 5% based on the total mass of the electrolyte. In some embodiments, the mass content of fluorosulfonate may be selected from 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or a value within the range of any two of the above points, based on the total mass of the electrolyte.
[0107] It is understandable that fluorosulfonates can participate in the formation of the SEI film and consume some of the fluorosulfonates, resulting in a decrease in the fluorosulfonate content in the electrolyte. For example, the mass content of fluorosulfonates in the electrolyte is detected as 0.001% (the mass content of fluorosulfonates in the electrolyte can be detected by referring to the General Rules for Ion Chromatography Analysis in Modern Analytical Instruments (JY / T 020-1996, issued on January 23, 1997, and implemented on April 1, 1997)). Therefore, based on the total mass of the electrolyte, the mass content of fluorosulfonates of 0.001% to 5% is within the scope protected in the embodiments of this application.
[0108] Controlling the mass content of fluorosulfonate within a suitable range is beneficial for forming components containing fluorine and sulfur elements in the SEI film, thereby effectively improving the overall stability of the interfacial SEI film. At the same time, it reduces the solubility of the interfacial SEI film in the electrolyte, thus greatly reducing the degree of gas production and improving the cycle performance and storage performance of sodium secondary batteries. It also reduces the impact of excessively high fluorosulfonate mass content on the fast-charging performance of sodium secondary batteries due to excessively high electrolyte conductivity.
[0109] In some embodiments, the mass content of fluorosulfonate is 0.1% to 2% based on the total mass of the electrolyte.
[0110] Further controlling the mass content of fluorosulfonate to 0.1%~2% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0111] In some embodiments, the mass content of difluorophosphate is 0.001% to 5% based on the total mass of the electrolyte. In some embodiments, the mass content of difluorophosphate may be selected from 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or a value within the range of any two of the above based on the total mass of the electrolyte.
[0112] It is understandable that difluorophosphate can participate in the formation of the SEI film and consume some of the difluorophosphate, resulting in a decrease in the difluorophosphate content in the electrolyte. For example, the mass content of difluorophosphate in the electrolyte is detected as 0.001% (the mass content of difluorophosphate in the electrolyte can be detected by referring to the General Rules for Ion Chromatography Analysis in Modern Analytical Instruments (JY / T 020-1996, issued on January 23, 1997, and implemented on April 1, 1997)). Therefore, based on the total mass of the electrolyte, the mass content of difluorophosphate is between 0.001% and 5%, which is within the scope protected in the embodiments of this application.
[0113] Controlling the mass content of difluorophosphate within a suitable range is beneficial for forming components containing fluorine and phosphorus elements in the SEI membrane, thereby effectively improving the overall stability of the interface SEI membrane. At the same time, it reduces the solubility of the interface SEI membrane in the electrolyte, thus greatly reducing the degree of gas production and improving the cycle performance and storage performance of sodium secondary batteries.
[0114] In some implementations, the mass content of difluorophosphate is 0.1% to 2% based on the total mass of the electrolyte.
[0115] Further controlling the mass content of difluorophosphate to 0.1%~2% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0116] In some embodiments, the electrolyte further includes a third additive, which includes one or more of the following: fluoroethylene carbonate, difluoroethylene carbonate, vinylene carbonate, ethylene ethylene carbonate, maleic anhydride, succinic anhydride, and triallyl phosphate.
[0117] In some embodiments, the third additive includes fluoroethylene carbonate. In some embodiments, the third additive includes vinylene carbonate. In some embodiments, the third additive includes maleic anhydride. In some embodiments, the third additive includes succinic anhydride. In some embodiments, the third additive includes triallyl phosphate.
[0118] The introduction of a third additive containing unsaturated functional groups is beneficial for the formation of a more soluble SEI film on the surface of the negative electrode sheet, which is more advantageous than the formation of a solvent in the electrolyte. This reduces the overall solubility of the SEI film in the electrolyte, thereby reducing the degree to which the negative electrode sheet is exposed to the electrolyte, and thus reducing the degree of gas production. This comprehensively improves the performance and lifespan of sodium secondary batteries.
[0119] In some embodiments, the mass content of the third additive is 0.01% to 10% based on the total mass of the electrolyte. In some embodiments, the mass content of the third additive may be selected from 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 4%, 5%, 6%, 8%, 10%, or a value within the range of any two of the above, based on the total mass of the electrolyte.
[0120] By controlling the mass content of the third additive within a suitable range, sufficient amounts of the third additive can be provided to form a SEI film with higher solubility, thereby reducing the overall solubility of the SEI film in the electrolyte, reducing the degree of exposure of the negative electrode sheet in the electrolyte, and thus reducing the degree of gas production, thereby comprehensively improving the performance of the battery.
[0121] In some implementations, the mass content of the third additive is 0.1% to 5% based on the total mass of the electrolyte.
[0122] Controlling the mass content of the third additive to 0.1%~5% is beneficial to balancing the storage performance and fast charging performance of sodium secondary batteries, thereby comprehensively improving the performance of sodium secondary batteries.
[0123] In some embodiments, the electrolyte includes a sodium salt, which includes one or more of NaPF6, NaBF4, NaN(SO2F)2, NaClO4, Na containing fluorine and phosphorus elements, such as AsF6, NaB(C2O4)2, and NaBF2(C2O4).
[0124] In some embodiments, the sodium salt includes NaPF6. In some embodiments, the sodium salt includes NaBF4. In some embodiments, the sodium salt includes NaFSI. In some embodiments, the sodium salt includes both NaPF6 and NaFSI. In some embodiments, the sodium salt includes both NaPF6 and NaClO4.
[0125] In some embodiments, the electrolyte includes a solvent, which includes one or more of the following: chain carbonate solvents, chain carboxylic acid ester solvents, cyclic carbonate solvents, and ether solvents.
[0126] In some embodiments, the chain carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate.
[0127] In some embodiments, the chain carboxylic acid ester solvent includes one or more of methyl formate, ethyl formate, methyl propionate, ethyl propionate, propyl propionate, ethyl butyrate, methyl acetate, ethyl acetate, and propyl acetate.
[0128] In some embodiments, the cyclic carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, butene carbonate, vinylene carbonate, fluoroethylene carbonate, ethylene sulfite, propylene sulfite, vinylethylene carbonate, 4-ethynyl-1,3-dioxacyclopentan-2-one, cis-4,5-difluoro-1,3-dioxacyclopentan-2-one, and trans-4,5-difluoro-1,3-dioxacyclopentan-2-one.
[0129] In some embodiments, the ether solvent includes one or more of dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, 1,2-diethoxyethane, and 1,2-dibutoxyethane.
[0130] [Positive electrode plate] The positive electrode includes a positive current collector and a positive electrode material layer located on at least one side of the positive current collector.
[0131] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode material layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0132] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0133] In some embodiments, the positive electrode material layer includes a positive electrode active material, which may be a known positive electrode active material for batteries. As an example, the positive electrode active material may include at least one of the following materials: layered transition metal oxides, polyanionic compounds, or Prussian blue compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. The Prussian blue compound includes Na. xP[R(CN)6] δ ·zH2O, wherein P and R each independently include at least one of transition metal elements, 0<x≤2, 0<δ≤1 and 0≤z≤10; the polyanionic compound includes Na b Me c (PO4) d O2X, wherein Me includes one or more of Ti, Cr, Mn, Fe, Co, Ni, V, Cu and Zn, X includes one or more of F, Cl and Br, 0<b≤4, 0<c≤2, 1≤d≤3.
[0134] In some embodiments, the positive electrode active material includes a layered transition metal oxide.
[0135] In some embodiments, the layered transition metal oxide includes Na x Mn a Fe b Ni c M d N e O 2-δ Q f , wherein M includes at least one of Ti, Li, V, Cr, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, Mg and Al, N includes at least one of Si, P, B, S and Se, Q includes at least one of F, Cl and N, 0.66≤x≤1, 0<a≤0.7, 0<b≤0.7, 0<c≤0.23, 0≤d<0.3, 0≤e≤0.3, 0≤f≤0.3, 0≤δ≤0.3, a+b+c+d+e=1, 0<e+f≤0.3, 0<(e+f) / a≤0.3, 0.2≤d+e+f≤0.3, (b+c) / a≤1.5.
[0136] The layered transition metal oxide positive electrode active material has the advantage of high voltage, but the transition metal therein will catalyze the oxidation of the solvent in the electrolyte to form RH + , since RH + is not resistant to reduction, the exposure of the negative electrode sheet will also cause the RH that migrates to the surface of the negative electrode sheet + to be reduced to form components that are not resistant to oxidation, which aggravates gas generation on the negative electrode sheet side. Through the combined use of the first additive and the second additive, various components in the formed SEI film cooperate with each other, which is beneficial to improving the overall stability of the interfacial SEI film, while reducing the overall dissolution degree of the interfacial SEI film in the electrolyte, reducing the exposure degree of the negative electrode sheet to the electrolyte, thereby greatly reducing the degree of gas generation, and comprehensively improving the cycle performance and storage performance of the sodium secondary battery.
[0137] In some embodiments, the positive electrode active material may not contain the Cu element.
[0138] In some embodiments, the positive electrode active material comprises a layered transition metal oxide containing Cu; the ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Cu in the positive electrode active material is greater than or equal to 0.002. In some embodiments, the ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Cu in the positive electrode active material may be selected as 0.002, 0.004, 0.005, 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 10, 50, 100, 500, 1000, 2000, 5000, or a value within a range consisting of any two of the above points.
[0139] In some embodiments, the positive electrode active material includes Na[Cu] 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2, Na 7 / 9 [Cu 2 / 9 Fe 1 / 9Mn 2 / 3 O2, NaNi 0.7 Co 0.15 Mn 0.15 At least one of O2.
[0140] It is understandable that introducing Cu into the positive electrode active material is beneficial to the stability of the positive electrode active material structure and improves the cycle performance of sodium secondary batteries. However, at the same time, Cu in the positive electrode active material will undergo a change in valence state under high pressure, producing Cu... 3+ Cu 3+ High oxidizing activity can accelerate electrolyte decomposition, thereby deteriorating the performance of sodium secondary batteries. However, cyclic ester compounds containing sulfur in the electrolyte can oxidize with Cu in the positive electrode active material at the positive electrode interface to form insoluble Cu salts, which helps reduce the degree of gas generation caused by electrolyte decomposition on the positive electrode side. Controlling the ratio of the mass content of cyclic ester compounds in the electrolyte to the mass content of Cu in the positive electrode active material within an appropriate range can effectively reduce the degree of gas generation caused by electrolyte decomposition on the positive electrode side.
[0141] In some embodiments, the mass content of Cu in the positive electrode active material is less than or equal to 23%. In some embodiments, the mass content of Cu in the positive electrode active material can be selected as 1%, 2%, 5%, 7%, 10%, 12%, 15%, 18%, 20%, 23%, or a value within a range consisting of any two of the above.
[0142] Controlling the Cu content in the positive electrode active material within a suitable range is beneficial for providing enough Cu to increase the stability of the positive electrode active material structure, while also reducing the degree of performance degradation of sodium secondary batteries caused by excessive Cu content leading to oxidative decomposition in the electrolyte.
[0143] In some embodiments, the Cu element content in the positive electrode active material is 6.5% to 18% by mass.
[0144] Further controlling the Cu content in the positive electrode active material layer to 6.5%~18% is beneficial to further balance the storage performance and fast charging performance of sodium secondary batteries.
[0145] In some embodiments, the positive electrode material layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0146] In some embodiments, the positive electrode material layer may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0147] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0148] [Negative electrode plate] The negative electrode includes a negative current collector and a negative electrode material layer located on at least one side of the negative current collector.
[0149] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0150] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0151] The negative electrode material layer also includes a negative electrode active material, which includes one or more of hard carbon, metallic sodium, sodium-tin alloy, and metal oxides.
[0152] The aforementioned negative electrode active materials all possess excellent sodium storage capacity, enabling sodium secondary batteries to have high energy density.
[0153] In some embodiments, the negative electrode material layer further includes Ca element; the ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Ca element in the negative electrode material layer is greater than or equal to 1. In some embodiments, the ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Ca element in the negative electrode material layer can be selected as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, or a value within a range consisting of any two of the above points.
[0154] Introducing calcium (Ca) into the negative electrode active material helps reduce the formation of sodium dendrites. Simultaneously, the introduction of Ca facilitates the formation of a Ca-containing SEI film with sulfur-containing cyclic ester compounds, thereby improving the overall toughness of the SEI film and reducing the DC impedance of the sodium secondary battery. Maintaining the ratio of the mass content of cyclic ester compounds in the electrolyte to the mass content of Ca in the negative electrode material layer within a suitable range allows for a balance between the storage performance and fast-charging performance of the sodium secondary battery.
[0155] In some embodiments, the mass content of Ca in the negative electrode material layer is 0.1 ppm to 3000 ppm. In some embodiments, the mass content of Ca in the negative electrode material layer can be selected from 0.1 ppm, 0.5 ppm, 1 ppm, 5 ppm, 10 ppm, 50 ppm, 100 ppm, 200 ppm, 400 ppm, 500 ppm, 600 ppm, 800 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, or a value within the range formed by any two of the above.
[0156] In some embodiments, the mass content of cyclic ester compounds in the electrolyte is 0.01% to 5%, and the mass content of Ca in the negative electrode material layer is 0.1 ppm to 3000 ppm. As an example, the ratio of the mass content of cyclic ester compounds in the electrolyte to the mass content of Ca in the negative electrode material layer can be 0.1% / 10ppm = 100, 1% = 10000 ppm.
[0157] It is understood that the Ca element in the negative electrode material layer can participate in the formation of the SEI film and consume some of the Ca element, resulting in a decrease in the mass content of the Ca element in the negative electrode material layer. For example, the mass content of the Ca element in the negative electrode material layer can be reduced to 1 ppm. Therefore, based on the total mass of the negative electrode material layer, the mass content of the Ca element is 0.1 ppm to 3000 ppm, which is within the range protected in the embodiments of this application.
[0158] Controlling the Ca content in the negative electrode material layer within a suitable range can generate calcium salt components in the SEI film, improving the overall toughness of the SEI film and reducing the DC resistance of the sodium secondary battery. It can also reduce the risk of negative electrode failure caused by excessive Ca content in the negative electrode material layer leading to gelation of the slurry during the preparation of the negative electrode sheet, the degree of reduction in first-time efficiency and the degree of aggravation of gas production caused by Ca(OH)2 formation during the preparation process, or the degree of performance degradation of the sodium secondary battery caused by the increase in DC resistance. This balances the storage performance and fast-charging performance of the sodium secondary battery.
[0159] In some embodiments, the mass content of Ca in the negative electrode material layer is 50ppm to 1000ppm.
[0160] In some embodiments, the mass content of Ca in the negative electrode material layer is 100ppm to 1000ppm.
[0161] Further controlling the mass content of Ca in the negative electrode material layer to 50ppm~1000ppm or 100ppm~1000ppm is beneficial to further improve the storage performance and fast charging performance of sodium secondary batteries.
[0162] In some implementations, at a charging rate of 0.05C, the capacity of the negative electrode in the charging range of 0.5V to 1V is 9mAh / g to 140mAh / g.
[0163] Within the charging range of 0.5V to 1V, controlling the capacity of the negative electrode within a suitable range can provide sufficient capacity to meet the energy density requirements of sodium secondary batteries, while also reducing the degree of performance degradation caused by excessive gas production due to excessive negative electrode capacity.
[0164] In this paper, the capacity of the negative electrode sheet can be tested using any known method within the charging range of 0.5V to 1V. As an example, the negative electrode sheet is punched into a small circular piece with a diameter of 14mm, and a sodium metal sheet is used as the negative electrode, a polypropylene film as the separator, and the electrolyte in some embodiments is used as the test electrolyte to assemble a button cell. Constant current charge-discharge tests are performed in the voltage range of 0.005-2V. During the discharge process, the constant current is sequentially discharged to 0.005V at a rate of 0.05C, 40μA, and 10μA. During the charging process, the constant current is charged to 2V at a rate of 0.05C. The specific capacity (mAh / g) during the charging process from 0.5V to 1V is recorded as the capacity of the negative electrode from 0.5V to 1V.
[0165] In this paper, the term "specific capacity" refers to the actual capacity exerted by a unit mass of negative electrode active material.
[0166] In some implementations, at a charging rate of 0.05C, the capacity of the negative electrode in the charging range of 0.5V to 1V is 18mAh / g to 70mAh / g.
[0167] Within the charging range of 0.5V to 1V, further controlling the capacity of the negative electrode sheet to 18mAh / g to 70mAh / g is beneficial for further balancing the energy density and storage performance of sodium secondary batteries.
[0168] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0169] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0170] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0171] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0172] [Isolation membrane] In some embodiments, the sodium secondary battery also includes a separator. Any known porous separator with good chemical and mechanical stability can be selected.
[0173] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.
[0174] Sodium secondary battery In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0175] In some embodiments, the sodium secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0176] In some embodiments, the outer packaging of a sodium secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of a sodium secondary battery can also be a soft pack, such as a pouch. The soft pack can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0177] The sodium secondary battery described in this application can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 This is an example of a square-structured sodium secondary battery.
[0178] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. The positive electrode, negative electrode, and separator can be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The sodium secondary battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.
[0179] In some embodiments, sodium secondary batteries can be assembled into battery modules, and the number of sodium secondary batteries contained in a battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.
[0180] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3In battery module 4, multiple sodium secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple sodium secondary batteries 5 can be fixed in place using fasteners.
[0181] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of sodium secondary batteries 5 are received.
[0182] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0183] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0184] In addition, this application also provides an electrical device, which includes at least one of the sodium secondary battery, battery module, or battery pack provided in this application. The sodium secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0185] As the electrical device, a sodium secondary battery, battery module, or battery pack can be selected according to its usage requirements.
[0186] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of sodium-ion batteries for this device, a battery pack or battery module can be used.
[0187] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use sodium-ion batteries as their power source.
[0188] Example The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0189] I. Preparation Method Example 1 1) Electrolyte In an argon-atmospheric glove box (H2O content <10 ppm, O2 content <1 ppm), propylene carbonate (PC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of 30 / 70, and 1M NaPF6 sodium salt was dissolved. Then, the compound with the structure shown in Formula I-8 (first additive) and sodium fluorosulfonate (second additive) were added and stirred until homogeneous to prepare the electrolyte. Based on the total mass of the electrolyte, the mass content of the compound with the structure shown in Formula I-1 (first additive) was 0.01%, and the mass content of sodium fluorosulfonate (second additive) was 0.5%.
[0190] 2) Preparation of positive electrode sheet Na 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 Preparation of O2 (13% Cu): 0.39M Na2CO3, 0.22M CuO, 0.06M Fe2O3, and 0.67M MnO2 precursors were ball-milled in a ball mill for 12 hours with ethanol as the dispersant. After drying, the uniformly mixed powder was pressed into tablets at 20 MPa and sintered at 900℃ for 12 hours to obtain the product. The sintered powder needs to be quickly transferred to a glove box for storage. The above-mentioned positive electrode active material Na 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material is evenly coated onto a 13μm thick positive current collector aluminum foil; after the aluminum foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet.
[0191] 3) Preparation of negative electrode sheet The negative electrode active material H2 (the negative electrode capacity in the 0.5V~1V charging range is 40mAh / g): the biomass material was calcined at 800℃ for 2h in a tube furnace with an argon atmosphere, then washed and dried with hydrochloric acid and deionized water respectively, ground and calcined at 1550℃ for 4h in a tube furnace with an argon atmosphere. The above-mentioned negative electrode active material H2, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na) and CaO were thoroughly mixed in a deionized water solvent system at a weight ratio of 89.987:3.999:4:2:0.014 to obtain a negative electrode slurry; the negative electrode slurry was then mixed at a rate of 0.14 g (dry weight) / 1540.25 mm. 2 The amount of coating is uniformly coated on a negative electrode current collector copper foil with a thickness of 8μm; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the negative electrode sheet.
[0192] 4) Separating membrane A 12μm porous polyethylene (PE) polymer film was used as the separator.
[0193] 5) Battery manufacturing The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to isolate them. The cells are then wound to obtain a bare cell. The tabs are welded on, and the bare cell is placed in an outer package. The electrolyte prepared above is injected into the dried cell. After processes such as encapsulation, settling, formation, shaping, and capacity testing, the sodium secondary battery product of Example 1 is obtained.
[0194] The secondary batteries of Examples 2-41 and Comparative Examples 1-4 are prepared in a similar manner to the secondary battery of Example 1, but the composition of the battery electrodes and the product parameters are adjusted. The different product parameters are detailed in Tables 1-3. In Examples 2-11 and 18-22, the mass content of the first additive, the second additive, and the third additive can be adjusted by adjusting the content of the solvent in the electrolyte. In Examples 30-33, the negative electrode material layers containing different mass contents of Ca can be controlled by adding different mass contents of CaO during the preparation of the negative electrode sheet. In Examples 34-37, the capacity of the negative electrode sheet can be effectively controlled by changing the carbonization temperature of the negative electrode material during the preparation process and by combining negative electrode materials with different capacities, as detailed below: Preparation of negative electrode active material H1 (the negative electrode capacity in the charging range of 0.5V~1V is 140mAh / g): Biomass material was calcined at 800℃ for 2h in a tube furnace with argon atmosphere, then washed and dried with hydrochloric acid and deionized water respectively, ground and calcined at 1150℃ for 2h in a tube furnace with argon atmosphere. The negative electrode active material H3 (the negative electrode capacity in the 0.5V~1V charging range is 9mAh / g): The biomass material was calcined at 800℃ for 2h in a tube furnace with an argon atmosphere, then washed and dried with hydrochloric acid and deionized water respectively, ground and calcined at 1650℃ for 6h in a tube furnace with an argon atmosphere to obtain the target material. Increasing the pyrolysis temperature further reduced defects and induced the formation of a large number of ordered micropores. The specific capacity in the 0.5V~1V range is about 9mAh / g. Example 34: The negative electrode active material H3, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na) and CaO were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2:0.014 to obtain a negative electrode slurry; the negative electrode slurry was then mixed at a rate of 0.14 g (dry weight) / 1540.25 mm. 2 The amount of coating is uniformly coated on a negative electrode current collector copper foil with a thickness of 8μm; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and cut to obtain the negative electrode sheet; Example 35: 70% H3 and 30% H2 negative electrode active materials, acetylene black conductive agent, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC-Na) thickener, and CaO were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2:0.014 to obtain a negative electrode slurry; the negative electrode slurry was then mixed at a rate of 0.14 g (dry weight) / 1540.25 mm. 2 The amount of coating is uniformly coated on a negative electrode current collector copper foil with a thickness of 8μm; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and cut to obtain the negative electrode sheet; Example 36: 30% H1 and 70% H2 of the negative electrode active materials, acetylene black as the conductive agent, styrene-butadiene rubber (SBR) as the binder, sodium carboxymethyl cellulose (CMC-Na) as the thickener, and CaO were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2:0.014 to obtain a negative electrode slurry; the negative electrode slurry was then mixed at a rate of 0.14 g (dry weight) / 1540.25 mm. 2 The amount of coating is uniformly coated on a negative electrode current collector copper foil with a thickness of 8μm; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and cut to obtain the negative electrode sheet; Example 37: The negative electrode active material H1, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na) and CaO were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2:0.014 to obtain a negative electrode slurry; the negative electrode slurry was then mixed at a rate of 0.14 g (dry weight) / 1540.25 mm. 2 The amount of coating is uniformly coated on a negative electrode current collector copper foil with a thickness of 8μm; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the negative electrode sheet.
[0195] Examples 38-41 show that positive electrode active materials containing different mass contents of Cu can be obtained by controlling the stoichiometric ratio of the precursors Fe2O3, CuO, MnO2, and Na2CO3 during the sintering process, as well as by the compounding of positive electrode active materials with different Cu contents during the preparation of the positive electrode sheet, as detailed below: Na 1 / 2 Fe 1 / 2 Mn 1 / 2 Preparation of O2 (0%Cu): 0.25M Na2CO3, 0.25M Fe2O3 and 0.5M MnO2 precursors were ball-milled in a ball mill for 12 hours with ethanol as the dispersant. After drying, the uniformly mixed powder was pressed into tablets at 20MPa and sintered at 900℃ for 12 hours to obtain the product. The sintered powder needs to be quickly transferred to a glove box for storage. Na 9 / 10 Cu 2 / 5 Fe 1 / 10 Mn 1 / 2 Preparation of O2 (23% Cu): 0.45M Na2CO3, 0.4M CuO, 0.05M Fe2O3, and 0.5M MnO2 precursors were ball-milled in a ball mill for 12 hours with ethanol as the dispersant. After drying, the uniformly mixed powder was pressed into tablets at 20 MPa and sintered at 900℃ for 12 hours to obtain the product. The sintered powder needs to be quickly transferred to a glove box for storage. Example 38: Using Na as the positive electrode active material 1 / 2 Fe 1 / 2 Mn 1 / 2 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material was evenly coated onto a 13μm thick positive electrode current collector aluminum foil; after the aluminum foil was dried at room temperature, it was transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet; Example 39: The positive electrode active material contains 50% Na 1 / 2Fe 1 / 2 Mn 1 / 2 O2, 50% Na 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material was evenly coated onto a 13μm thick positive electrode current collector aluminum foil; after the aluminum foil was dried at room temperature, it was transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet; Example 40: 50% Na+ positive electrode active material 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, 50% Na 9 / 10 Cu 2 / 5 Fe 1 / 10 Mn 1 / O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material was evenly coated onto a 13μm thick positive electrode current collector aluminum foil; after the aluminum foil was dried at room temperature, it was transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet; Example 41: Using Na as the positive electrode active material 9 / 10 Cu 2 / 5 Fe 1 / 10 Mn 1 / 2 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material is evenly coated onto a 13μm thick positive current collector aluminum foil; after the aluminum foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet.
[0196] II. Performance Testing 1. Electrolyte 1) Mass content test of the first additive The detection of the first additive can be performed qualitatively and quantitatively by gas chromatography of organic components, referring to GB / T 6041-2002 and GB / T 9722-2006.
[0197] 2) Mass content test of the second additive The detection of the second additive can be carried out in accordance with the General Rules for Ion Chromatography Analysis (JY / T 020-1996, issued on January 23, 1997, and implemented on April 1, 1997) in the General Rules for Analytical Instrumentation Methods of Modern Analytical Instrumentation, using ion chromatography analysis to test and analyze the components and content.
[0198] 3) Mass content test of the third additive The detection of the third additive can be performed qualitatively and quantitatively by gas chromatography of organic components, referring to GB / T 6041-2002 and GB / T 9722-2006.
[0199] 2. Negative electrode plate / Positive electrode plate 1) Determination of Ca content in the negative electrode material layer The Ca content in the anode material was tested according to the general rule EPA 6010D-2014, using inductively coupled plasma atomic emission spectrometry.
[0200] 2) Determination of Cu content in positive electrode active material The Cu content in the positive electrode active material was determined according to the general rule EPA 6010D-2014, using inductively coupled plasma atomic emission spectrometry.
[0201] 3) Capacity test of negative electrode in the 0.5V~1V range The negative electrode sheet was punched into small circular pieces with a diameter of 14 mm. A sodium metal sheet was used as the negative electrode, and a polypropylene membrane was used as the separator. A 1.3 mol / L sodium hexafluorophosphate solution was used as the electrolyte. The electrolyte contained ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a mass ratio of 1:2:2. This electrolyte was used to assemble button batteries. Constant current charge-discharge tests were conducted in the voltage range of 0.005-2V. During the discharge process, the batteries were discharged at constant current rates of 0.05C, 40μA, and 10μA to 0.005V. During the charging process, the batteries were charged at constant current rates of 0.05C to 2V. The specific capacity (mAh / g) during the charging process between 0.5-1V was recorded as the capacity of the negative electrode from 0.5 to 1V.
[0202] 3. Battery 1) Low-pressure storage volume change rate At 25°C, the novel sodium secondary batteries prepared in the examples and comparative examples were left to stand for 5 minutes, then charged at a constant current of 1C to 4.0V, and then charged at a constant voltage until the current was less than or equal to 0.05C. After that, they were left to stand for 5 minutes, and then discharged at a constant current of 1C to 1.5V. The volume V1 of the battery was tested by the water displacement method. Then the battery was placed in a 60°C oven and stored for 2 months. After that, the battery was taken out and the volume was tested as V2. The volume change rate of the battery was = (V2-V1) / V1×100%.
[0203] 2) Charging performance at -10℃ Fabrication of a three-electrode battery: First, a sodium vanadium phosphate reference electrode is prepared. The active material sodium vanadium phosphate, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed thoroughly in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to form a slurry. The slurry is then uniformly coated onto a 10cm long aluminum wire (with a 1cm coating area). After drying at 100℃, the target reference electrode is obtained. During the fabrication of the sodium secondary battery, the above reference electrode is placed between the anode and the separator to obtain the three-electrode battery. -10℃ Charging Performance Test: At 25℃, the battery was charged at a constant current of 0.1C to a voltage of 4.0V, then charged at a constant voltage until the current was less than or equal to 0.05C. After resting for 5 minutes, it was discharged at a constant current of 0.1C to 1.5V, and the discharge capacity was recorded as C1. Then, the battery was placed in a -10℃ environment and left to stand for 2 hours. It was then charged at a constant current of 0.1C to a voltage of 4.0V. The charging capacity when the negative electrode potential was compared with the reference potential of -3.377V was obtained as C2. The charging performance of the battery at -10℃ = C2 / C1×100%.
[0204] 3) DC impedance At -25℃, adjust the state of charge of a single battery cell to 50% SOC, let it stand for 30 minutes, and record the battery voltage at this time as U1 (V). Discharge at 0.36C for 10 seconds, and record the battery voltage at this time as U2 (V). The corresponding battery discharge current I (mA) is 0.36 × battery design capacity (mAh). DC impedance DCR (mΩ) = (U1 - U2) / I.
[0205] 4) Cyclic performance At 25°C, the prepared battery was charged to 4.0V with a constant current of 0.5C, then charged to 0.05C with a constant voltage of 4.0V until the current dropped to 0.05C. After standing for 10 minutes, it was discharged to 1.5V with a constant current of 1C. This is the first charge / discharge cycle of the battery, and the discharge capacity of this cycle is recorded as the discharge capacity (C0) of the battery in the first cycle. The above steps were repeated for the same battery. The discharge capacity (C1) of the battery after 300 cycles was recorded. The capacity retention rate after 300 cycles is calculated as C1 / C0 × 100%. The testing process for the comparative example and other embodiments is the same as above.
[0206] III. Analysis of Test Results for Each Embodiment and Comparative Example Batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1-4 below.
[0207] Table 1 Preparation Parameters
[0208] Table 2 Preparation Parameters
[0209] Table 3 Preparation Parameters
[0210] Table 4 Performance Test Table
[0211] In Examples 1-41, the electrolyte in the sodium secondary battery includes a first additive and a second additive. The first additive includes compounds with the structures shown in Formula I-1, Formula I-8, Formula I-17, Formula I-26 or Formula I-33. The second additive includes sodium fluorosulfonate, sodium difluorophosphate, lithium difluorophosphate or aluminum fluorosulfonate.
[0212] As can be seen from the comparison between Examples 1-17 and Comparative Example 1, the addition of the first additive and the second additive to the electrolyte is beneficial to reducing the volume expansion rate and DC resistance of the sodium secondary battery after high-temperature storage, as well as improving its charging performance and cycle capacity retention rate.
[0213] As can be seen from the comparison of Examples 3, 6-10, 16-17 with Comparative Example 2, Examples 1-5, 13-15 with Comparative Example 3, and Examples 11-12 with Comparative Example 4, compared with electrolytes containing only the first additive or the second additive, the electrolyte in this application contains both the first additive and the second additive, which is beneficial to reducing the volume expansion rate of sodium secondary batteries after high-temperature storage and improving the cycle capacity retention rate of sodium secondary batteries.
[0214] As seen in Examples 1-10, controlling the mass ratio of the compound with the structure shown in Formula I-1 to the sodium fluorosulfonate as the second additive is 0.02-200 to ensure that the sodium secondary batteries exhibit excellent storage performance, cycle performance, and charging performance. A comparison of Examples 2-5 and 7-10 with Examples 1 and 6 shows that controlling the mass ratio of the compound with the structure shown in Formula I-1 to the sodium fluorosulfonate as the second additive is 0.2-100, which is beneficial for balancing the storage performance, cycle performance, and charging performance of the sodium secondary batteries.
[0215] As can be seen from Examples 1-5, based on the total mass of the electrolyte, controlling the mass content of the compound with the structure shown in the first additive formula I-1 to be 0.01%~5% ensures that the sodium secondary batteries all exhibit excellent storage performance, cycle performance, and charging performance. A comparison of Examples 2-4 with Examples 1 and 5 shows that controlling the mass content of the compound with the structure shown in the first additive formula I-1 to be 0.1%~2% is beneficial for balancing the storage performance, cycle performance, and charging performance of the sodium secondary battery.
[0216] As seen in Examples 3, 6-10, based on the total mass of the electrolyte, controlling the mass content of the second additive, sodium fluorosulfonate, to be 0.001%~5% ensures that the sodium secondary batteries exhibit excellent storage performance, cycle performance, and charging performance. A comparison of Examples 3, 7-8 with Examples 6, 9-10 shows that controlling the mass content of the second additive, sodium fluorosulfonate, to be 0.1%~2% is beneficial for balancing the storage performance, cycle performance, and charging performance of the sodium secondary batteries.
[0217] As can be seen from Examples 3, 11-17, the first additive is selected from compounds with the structures shown in Formula I-1, Formula I-8, Formula I-17, Formula I-26 or Formula I-33, and the second additive is selected from sodium fluorosulfonate, sodium difluorophosphate, lithium difluorophosphate or aluminum fluorosulfonate, all of which can enable sodium secondary batteries to have excellent storage performance, cycle performance and charging performance.
[0218] As can be seen from the comparison between Examples 18-22, 24 and Example 11, and Examples 23, 25 and Example 3, the introduction of a third additive into the electrolyte, and the third additive being FEC, VC, VEC or maleic anhydride, all help to reduce the DC resistance of sodium secondary batteries and the volume expansion rate of sodium secondary batteries after high-temperature storage, thereby improving the charging performance and cycle capacity retention rate of sodium secondary batteries.
[0219] As seen in Examples 18-22, controlling the mass content of the third additive to 0.05%-10% based on the total mass of the electrolyte results in excellent storage, cycle, and charging performance in the sodium secondary batteries. A comparison of Examples 18, 20-21 with Examples 19, 22 shows that controlling the mass content of the third additive to 0.1%-5% is beneficial for balancing the storage, cycle, and charging performance of the sodium secondary battery.
[0220] As can be seen from Examples 11 and 26-27, the lithium salt in the electrolyte is NaFSI and / or NaPF6. When used in combination with the first additive and the second additive, both can enable sodium secondary batteries to have excellent storage performance, cycle performance and charging performance.
[0221] As can be seen from Examples 11 and 27-29, the solvent in the electrolyte is two or more of PC, EMC, DG, and EP. When used in combination with the first additive and the second additive, the sodium secondary battery can have excellent storage performance, cycle performance and charging performance.
[0222] As can be seen from Examples 11, 30-33, controlling the ratio of the mass content of the first additive in the electrolyte to the mass content of Ca in the negative electrode material layer to be greater than or equal to 1 can enable sodium secondary batteries to have excellent storage performance, cycle performance and charging performance.
[0223] As seen in Examples 11 and 30-33, controlling the Ca content in the negative electrode material layer to 50ppm-3000ppm, when used in combination with the first and second additives, results in excellent storage, cycle, and charging performance in sodium secondary batteries. A comparison of Examples 10 and 30-31 with Example 32 shows that further controlling the Ca content in the negative electrode material layer to 100ppm-3000ppm helps to further reduce the DC resistance of the sodium secondary battery and improve its charging performance and cycle capacity retention.
[0224] As seen in Examples 11 and 34-37, at a charging rate of 0.05C, controlling the capacity of the negative electrode within the charging range of 0.5V to 1V to 9mAh / g to 140mAh / g allows the sodium secondary battery to exhibit excellent storage, cycle, and charging performance. A comparison of Examples 11 and 35-36 with Examples 34 and 37 shows that further controlling the capacity of the negative electrode within the charging range of 0.5V to 1V to 18mAh / g to 70mAh / g is beneficial for further reducing the DC resistance of the sodium secondary battery and the volume expansion rate after high-temperature storage, thereby improving the charging performance and cycle capacity retention of the sodium secondary battery.
[0225] A comparison of Examples 11, 39-41 with Example 38 shows that introducing Cu into the positive electrode active material can improve the cycle capacity retention rate of sodium secondary batteries.
[0226] As can be seen from Examples 11, 39-41, controlling the ratio of the mass content of the first additive in the electrolyte to the mass content of Cu in the positive electrode active material to be greater than 0.002 can result in sodium secondary batteries exhibiting excellent storage performance, cycle performance, and charging performance.
[0227] As can be seen from Examples 11, 39-41, controlling the mass content of Cu in the positive electrode active material to be less than or equal to 23% results in excellent storage, cycle, and charging performance in sodium secondary batteries. A comparison between Examples 11, 39-40 and Example 41 shows that further controlling the mass content of Cu in the positive electrode active material to 6.5%-18% is beneficial for balancing the storage, cycle, and charging performance of sodium secondary batteries.
[0228] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A sodium secondary battery, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte. The electrolyte includes a first additive, which comprises a cyclic ester compound containing sulfur, and the cyclic ester compound includes compounds with the structure shown in Formula I. Equation I, In Equation I, R1 includes or R2 and R3 each independently include at least one of the following: hydrogen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, C1-C3 alkoxy group, C1-C3 haloalkoxy group, C1-C3 olefin group, ester group, cyano group, and sulfonic acid group; R4 includes at least one of the following: oxygen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, C1-C3 alkoxy group, and C1-C3 haloalkoxy group. The positive electrode includes a positive current collector and a positive electrode material layer located on at least one side of the positive current collector. The positive electrode material layer includes a positive electrode active material, which includes a layered transition metal oxide containing Cu.
2. The sodium secondary battery according to claim 1, characterized in that, In Formula I, R2 and R3 each independently include at least one of hydrogen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, and C1-C3 olefin group, and R4 includes at least one of oxygen atom, C1-C6 alkyl group, C1-C3 haloalkyl group, C1-C3 alkoxy group, and C1-C3 haloalkoxy group.
3. The sodium secondary battery according to claim 1, characterized in that, The structure shown in Formula I includes , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , At least one of them.
4. The sodium secondary battery according to any one of claims 1 to 3, characterized in that, The electrolyte also includes a second additive, which includes one or more of fluorosulfonate and difluorophosphate.
5. The sodium secondary battery according to claim 4, characterized in that, The fluorosulfonate includes compounds represented by Formula II. (FSO3) y1 M1 y1+ Formula II In Formula II, M1 y1+ Including Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the following, where y1 = 1, 2, or 3.
6. The sodium secondary battery according to claim 4, characterized in that, The difluorophosphate includes compounds represented by Formula III. (PO2F2) y2 M2 y2+ Formula III In Equation III, M2 y2+ Including Li + Na + K + 、Rb + Cs + Mg 2+ Ca 2+ Ba 2+ Fe 2+ Ni 2+ Al 3+ Fe 3+ Ni 3+ One or more of the following, y2 = 1, 2 or 3.
7. The sodium secondary battery according to claim 4, characterized in that, The mass ratio of the first additive to the second additive is 0.02 to 500.
8. The sodium secondary battery according to claim 7, characterized in that, The mass ratio of the first additive to the second additive is 0.2 to 100.
9. The sodium secondary battery according to any one of claims 1 to 8, characterized in that, Based on the total mass of the electrolyte, the mass content of the cyclic ester compound is 0.01% to 5%.
10. The sodium secondary battery according to claim 9, characterized in that, Based on the total mass of the electrolyte, the mass content of the cyclic ester compound is 0.1% to 2%.
11. The sodium secondary battery according to claim 5, characterized in that, Based on the total mass of the electrolyte, the mass content of the fluorosulfonate is 0.001% to 5%.
12. The sodium secondary battery according to claim 11, characterized in that, Based on the total mass of the electrolyte, the mass content of the fluorosulfonate is 0.1% to 2%.
13. The sodium secondary battery according to claim 6, characterized in that, Based on the total mass of the electrolyte, the mass content of the difluorophosphate is 0.001% to 5%.
14. The sodium secondary battery according to claim 13, characterized in that, Based on the total mass of the electrolyte, the mass content of the difluorophosphate is 0.1% to 2%.
15. The sodium secondary battery according to any one of claims 1 to 14, characterized in that, The electrolyte further includes a third additive, which includes one or more of the following: fluoroethylene carbonate, difluoroethylene carbonate, vinylene carbonate, ethylene ethylene carbonate, maleic anhydride, succinic anhydride, and triallyl phosphate.
16. The sodium secondary battery according to claim 15, characterized in that, Based on the total mass of the electrolyte, the mass content of the third additive is 0.01% to 10%.
17. The sodium secondary battery according to claim 16, characterized in that, Based on the total mass of the electrolyte, the mass content of the third additive is 0.1% to 5%.
18. The sodium secondary battery according to any one of claims 1 to 17, characterized in that, The electrolyte includes a sodium salt, which includes one or more of NaPF6, NaBF4, NaN(SO2F)2, NaClO4, NaAsF6, NaB(C2O4)2, NaBF2(C2O4), and NaFSI, and may be selected from one or more of NaPF6 and NaFSI.
19. The sodium secondary battery according to any one of claims 1 to 18, characterized in that, The electrolyte includes a solvent, which includes one or more of the following: chain carbonate solvents, chain carboxylic acid ester solvents, cyclic carbonate solvents, and ether solvents.
20. The sodium secondary battery according to claim 19, characterized in that, The chain carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate. The chain-like carboxylic acid ester solvent includes one or more of methyl formate, ethyl formate, methyl propionate, ethyl propionate, propyl propionate, ethyl butyrate, methyl acetate, ethyl acetate, and propyl acetate. The cyclic carbonate solvent includes one or more of the following: ethylene carbonate, propylene carbonate, butene carbonate, vinylene carbonate, fluoroethylene carbonate, ethylene sulfite, propylene sulfite, vinylethylene carbonate, 4-ethynyl-1,3-dioxacyclopentan-2-one, cis-4,5-difluoro-1,3-dioxacyclopentan-2-one, and trans-4,5-difluoro-1,3-dioxacyclopentan-2-one. The ether solvents include one or more of dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, 1,2-diethoxyethane, and 1,2-dibutoxyethane.
21. The sodium secondary battery according to any one of claims 1 to 20, characterized in that, The layered transition metal oxide includes Na x Mn a Fe b Ni c M d N e O 2-δ Q f Wherein, M includes at least one of Ti, Li, V, Cr, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, Mg, and Al; N includes at least one of Si, P, B, S, and Se; Q includes at least one of F, Cl, and N; 0.66 ≤ x ≤ 1; 0 <a≤0.7,0<b≤0.7,0<c≤0.23,0≤d<0.3,0≤e≤0.3,0≤f≤0.3,0≤δ≤0.3,a+b+c+d+e=1,0<e+f≤0.3,0<(e+f) / a≤0.3,0.2≤d+e+f≤0.3,(b+c) / a≤1.5。 22. The sodium secondary battery according to any one of claims 1 to 21, characterized in that, The ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Cu in the positive electrode active material is greater than or equal to 0.
002.
23. The sodium secondary battery according to any one of claims 1 to 22, characterized in that, The mass content of Cu element in the positive electrode active material is less than or equal to 23%.
24. The sodium secondary battery according to claim 23, characterized in that, The Cu element in the positive electrode active material has a mass content of 6.5% to 18%.
25. The sodium secondary battery according to any one of claims 1 to 24, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer located on at least one side of the negative electrode current collector, wherein the negative electrode material layer includes Ca element; The ratio of the mass content of the cyclic ester compound in the electrolyte to the mass content of Ca in the negative electrode material layer is greater than or equal to 1.
26. The sodium secondary battery according to claim 25, characterized in that, The mass content of Ca in the negative electrode material layer is 0.1ppm to 3000ppm.
27. The sodium secondary battery according to claim 25, characterized in that, The mass content of Ca in the negative electrode material layer is 50ppm to 1000ppm.
28. The sodium secondary battery according to claim 25, characterized in that, The mass content of Ca in the negative electrode material layer is 1000ppm~3000ppm.
29. The sodium secondary battery according to any one of claims 25 to 28, characterized in that, The negative electrode material layer also includes a negative electrode active material, which includes one or more of hard carbon, metallic sodium, tin alloy, and metal oxide.
30. The sodium secondary battery according to any one of claims 1 to 29, characterized in that, At a charging rate of 0.05C, the capacity of the negative electrode sheet, which is located in the charging range of 0.5V to 1V, is 9mAh / g to 140mAh / g.
31. The sodium secondary battery according to claim 30, characterized in that, At a charging rate of 0.05C, the capacity of the negative electrode sheet, which is located in the charging range of 0.5V to 1V, is 18mAh / g to 70mAh / g.
32. An electrical appliance, characterized in that, The sodium secondary battery includes any one of claims 1 to 31.
